Evaluation of Stylohyoid Ligament Calcifications in the Central Anatolian Region - Ali Altındağ (Journal of Community Medicine and Public Health Research)
This study aims to determine the prevalence of the elongated styloid process (ESP) on panoramic radiographs in a Turkish subpopulation and to investigate the relationship between SP lengths and the age and gender of individuals. Digital panoramic radiographs of 1000 patients who applied to Necmettin Erbakan University, Faculty of Dentistry, Dentomaxillofacial Radiology Clinic for the first examination between January 2020 and January 2022 were obtained from the database and examined. Individuals were evaluated by dividing them into three groups according to their age SP lengths were measured on both sides, and those greater than 30 mm were contemplated elongated. The data were evaluated in the SPSS V.21 program. In 1000 evaluated patients, ESP of >30 mm was detected in 304 individuals. It was determined that SP length did not differ according to age groups, gender, and systemic disease (p<0.05). Panoramic radiographs are useful, economical, and easily reachable diagnostic equipment in the diagnosis of symptomatic or asymptomatic ESP. Furthermore, it would be more useful to evaluate the prevalence of ESP with larger sample groups and advanced imaging methods.